Expected palaeoanthropological and archaeological signal from a Neolithic demographic transition on a worldwide scale - Bocquet-Appel, Jean-Pierre P. (Documenta Praehistorica, 2004)
A signal of major demographic change was detected from a palaeoanthropologicaldatabase of 68 Meso-Neolithic cemeteries in Europe (reduced to 36 due to a sampling bias). The signal is characteriyed by a relatively abrupt change in the proportion of immature skeletons (aged 5-19 years), relative to all buried skeletons (5 years +). From the Meso to the Neolithic, the proportion rose from approximately 20% to 30%. This change reflects a noticeable increase in the birth rate over a duration of about 500-700 years, and is referred to as the Neolithic Demographic Transition (NDT). Another category of independent archaeological data, on enclosures (N =694), which are interpreted as a response to population growth within the social area, reveals a similar signal at the same tempo. If this is a true signal, we should expect it to be detected also in all the independent centresof agricultural invention worldwide. The NDT is at the historical root of the pre-industrial populations that would gradually spread across the Earthand which are now rapidly disappearing.
Keywords: arheološka najdišča; arheološke najdbe; grobišča; demografske spremembe; demografski razvoj; kmetijstvo; agriculture; mezolitik; neolitik